Financial leverage and its impact on return and risk: an applied study in the Iraqi private service sector / an analytical study in Al-Mansour General Company - Mushtaq Abdul Amir Taleb (Iraqi Journal for Administrative Sciences, 2025)
the modern financial ideology cares about the relationship betweenreturn and riskbecauseitcause on the relationshipin the valueper shareand thenthevalue of the business, andis known that theyieldand the consequentriskdepending on therelationshipeternalbetweenreturn and risk, cannot befor them tobe independentandisolated fromothervariablesother particularly with regard to the composition ofthe financial structureanddeterminedfrom theratioof leverage. hencethis study toshedlight on the natureof leverageandrangesimpact onreturn and risk, through the application ofthe studyon theservice companiesprivatecontributionregisteredin the Iraqi marketfor securities, as it has beentakingsector Special servicesconsisting oftencompaniesduring the period(2006 -2011), Thestudyfounda set of conclusions , mainly correlated positively between variable leverage on the one hand and the return on investment and risk on the other hand, and against which possible to identify some recommendations including the need for attention to the positive correlation between return and risk, and the need to take the variables contained in a search by a combined when determining investment decisions and the distribution of profits.